PENGARUH E-PAYMENT, E-COMMERCE, DAN PENGETAHUAN AKUNTANSI TERHADAP KINERJA UMKM KOTA BATAM - Maries Huang; Risca Azmiana (LPPM Universitas Putera Batam, 2025)
This study examines the influence of e-payment, e-commerce, and accounting knowledge on the performance of MSMEs (Micro, Small, and Medium Enterprises) in Batam City. Data were collected through online questionnaires and direct interactions with 241 MSMEs located in the Bengkong and Lubuk Baja sub districts, as registered with the Cooperative Office of Batam City. From this population, 150 respondents were selected using the Slovin formula with a 5% margin of error to represent the sample. The data analysis was carried out using statistical methods, including descriptive analysis, instrument testing, classical assumption testing, multiple linear regression analysis, and hypothesis testing, processed using SPSS version 29. The results of the study indicate that e-payment, e-commerce, and accounting knowledge significantly influence the performance of MSMEs in Batam City. The conclusion based on the research findings confirms that H1 is accepted, H2 is accepted, H3 is accepted, and H4 is accepted.